Rickets in very low-birth-weight infants born at Baragwanath Hospital. - Zuckerman, Michele (My University, 1991)
Disturbed mineral and bone metabolism is frequently found in very low-birth-weight infants fed breast-milk during the first three months of life. The study was designed to assess the prevalence of this disturbed mineral homeostasis in a very low-birth-weight populatiun at Baragwanath Hospital and to determine whether the addition of a preterm infant formula to the feeds reduced the prevalence and increased the rate of weight gain. Fifty three neonates weighing less than 1200g born at Baragwanath Hospital were monitored for weight gain, growth and for biochemical and radiological evidence of metabolic bone disease. The infants were randomized to receive either breast-milk only feeds or a combination of breast-milk and a premature formula in order to assess the effect of the different feeds on the development of bone disease. Weight gain and growth were similar in both groups. Calcium and phosphorus intakes were higher in the mixed feeding group. However, serum calcium and phosphorus values were similar in the two groups throughout the study. The breast-milk group had significantly higher alkaline phosphatase levels. Radiological rickets was uncommun in both groups, although periosteal reactions and osteopenia occurred frequently and with similar prevalence in both groups. Overt rickets is not a major problem in very-low birth- weight infants born at Baragwanath Hospital, although raised serum alkaline phosphatase values occur frequently. Feeding with breast-milk and a premature infant formula in equal proportions (as opposed to breast-milk only) does not appear to have any effect on weight gain and growth in very low-birth-weight infants, but does partially prevent the pathological rise in alkaline phosphatase levels.
A Dissertation Submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg for the degree of Master of Medicine.
Keywords: Infant, Low Birth Weight.; Rickets in infancy & childhood.